LEGAL BASIS AND FORMS OF THE PROSECUTION'S PARTICIPATION IN THE CONDUCT OF CIVIL COURT CASES (Web of Teachers: Inderscience Research, 2024)
This article describes the concept, legal bases and forms of prosecutor's participation in civil court proceedings. Specific characteristics of the prosecutor's participation in civil court proceedings are analyzed theoretically and practically based on national legislation. At the same time, the opinions and opinions of the theoretician scientists, experienced practitioners in this field were analyzed.